Effects of teacher's feedback on freshmen's motivation in speaking lessons: A survey research at Hanoi University of Business and Technology = Ảnh Hưởng từ phản hồi của giaoc viên lên động lực học tập của sinh viên năm thứ nhất: Một nghiên cứu tìm hiểu tạ - Trương, Thị Hương (University of Languages and International Studies, 2017)
M.A. Thesis Teaching Methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2011